Fostering transparency in e‐cigarette research synthesis: the utility and limitations of methodological hierarchies. (8th February 2018) - Villanti, Andrea C.; Niaura, Raymond S.; Pearson, Jennifer L.; Glasser, Allison M.; Abrams, David B.
Abstract : Commentary to:How do we determine the impact of e‐cigarettes on cigarette smoking cessation or reduction? Review and recommendations for answering the research question with scientific rigor